2010
DOI: 10.1038/mp.2010.15
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor is critically involved in basal and fluoxetine-stimulated adult hippocampal cell proliferation and in anxiety, depression, and memory-related behaviors

Abstract: Intensive research is devoted to unravel the neurobiological mechanisms mediating adult hippocampal neurogenesis, its regulation by antidepressants, and its behavioral consequences. Macrophage migration inhibitory factor (MIF) is a pro-inflammatory cytokine that is expressed in the CNS, where its function is unknown. Here, we show, for the first time, the relevance of MIF expression for adult hippocampal neurogenesis. We identify MIF expression in neurogenic cells (in stem cells, cells undergoing proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 72 publications
10
84
3
Order By: Relevance
“…Although reduced neurogenesis and depression-like phenotypes arise in tandem following various chronic stressors (e.g., Surget et al, 2008;Bessa et al, 2009a), a requirement for reduced neurogenesis in the development of a depression-like phenotype has apparently been demonstrated only by Conboy et al (2011). In our hands, however, cD2 KO mice, devoid of adult brain neurogenesis, did not show increased immobility in FST and TST tests.…”
Section: Discussioncontrasting
confidence: 41%
“…Although reduced neurogenesis and depression-like phenotypes arise in tandem following various chronic stressors (e.g., Surget et al, 2008;Bessa et al, 2009a), a requirement for reduced neurogenesis in the development of a depression-like phenotype has apparently been demonstrated only by Conboy et al (2011). In our hands, however, cD2 KO mice, devoid of adult brain neurogenesis, did not show increased immobility in FST and TST tests.…”
Section: Discussioncontrasting
confidence: 41%
“…Neuronal proliferation induced by fluoxetine can be blocked by MIF inhibition and MIF knockout [78] , which suggests that MIF plays a role in the neurogenesis induced by antidepressants. Further studies have shown that the MIF-mediated cell proliferation is mediated by BDNF.…”
Section: The Hypothalamus-pituitary-adrenal Axis Hyperactivity Hypothmentioning
confidence: 96%
“…After treatment with antidepressants, the infl ammatory levels in the peripheral circulation as well as MIF expression levels in macrophages and lymphocytes are reduced [77] . Although MIF expressed by infl ammatory cells (such as macrophages) in the peripheral circulation can act against glucocorticoids and infl ammation, inhibition of MIF cannot stop depression; instead, it induces anxiety-and depression-like phenotypes in laboratory animals, leading to a decline in hippocampus-dependent learning and memory [78] . This indicates that high levels of MIF expressed by leukocytes in the peripheral circulation can facilitate the development of depression, and MIF expressed in the CNS is essential for neurogenesis, mood regulation, as well as learning and memory, which is contradictory to its role in infl ammatory cells of the peripheral circulation.…”
Section: The Hypothalamus-pituitary-adrenal Axis Hyperactivity Hypothmentioning
confidence: 99%
“…Both depression and PAH are characterized by increased levels of proinfl ammatory cytokines, such as interleukin-6 and tumor necrosis factor-a , which could refl ect a mechanistic link between these two disease processes. [33][34][35] These fi ndings are provocative, but whether there is a causal relationship between depression and the progression of PAH cannot be determined based on the present results. Alternatively, alleviation of depression could have a benefi cial effect on outcomes in PAH that is independent of any impact on pathogenic mechanisms; however, we were not able to evaluate any effect of SSRIs on depression in the present study.…”
Section: Unadjusted Outcomes: Mortality and Composite End Pointmentioning
confidence: 41%